THE SKILLS OF JAMBI FIELD EXTENSION OFFICERS (FEO) IN WRITING RESEARCH PAPERS - Denmar, Denny; Sari, Siti Rahma (Dinasti Publisher, 2020)
This research aimed to show a close relationship between: 1) The ability of verbal reasoning and the writing scientific papers skill; 2) Understanding of word selection and the writing scientific papers skill; 3) The ability to use cohesion devices and the writing scientific papers skill; 4) The ability of verbal reasoning, understanding of word selection, ability to use cohesion devices together with the writing scientific papers skill of Jambi FEO. This research used the method of survey with correlational technique. The sample of this research was 50 people who were the Civil Servants FEO, working at the Jambi Provincial Extension Office in 2019. The results showed a significant and linear relationship between 1. The verbal reasoning ability and the writing scientific papers skill, shown by the equation: ? = 23,15 + 0,81 X1 2. Understanding of word selection and the writing scientific papers skill, shown by the equation: ?=39,32 + 0,55 X2 3. The ability to use cohesion devices and the writing scientific papers skill, shown by the equation: ? = 40,02 + 0,57 X3 4. The verbal reasoning ability, understanding of word selection, ability to use cohesion devices together with the writing scientific papers skill, shown by the equation: ? = 21, 09 + 0,421 X1 + 0,16 X2 + 0,27 X3. The multiple correlation coefficient was Ry123 = 0.85, and the determination coefficient was R2 = 0.72, which means that 72% of variations in the scientific papers writing skill can be explained by the verbal reasoning ability, understanding of word selection, and the ability to use cohesion tools.